2021
DOI: 10.1002/2211-5463.13203
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A4 protects primary spinal cord neurons from Erastin‐induced ferroptosis by activating the Akt/Nrf2/HO‐1 signaling pathway

Abstract: Ferroptosis is an iron‐dependent programmed cell death, which participates in the pathogenesis of spinal cord injury (SCI). Our previous study has revealed that Lipoxin A4 (LXA4) exerts a protective role in SCI. Here, we investigated whether LXA4 can protect SCI through inhibiting neuronal ferroptosis. We treated primary spinal cord neurons with Erastin (ferroptosis activator) to induce ferroptosis. Erastin treatment reduced cell viability and enhanced cell death of primary spinal cord neurons, which was rescu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…That is, tagitin C induces ferroptosis through the activation of the PERK-NRF2-HO-1 signaling pathway mediated by ER [ 74 ]. In addition, there are other pathways related to NRF2 that regulate ferroptosis: GSK-3β/NRF2 signaling pathway [ 75 ], Akt/NRF2/HO-1 signaling pathway [ 76 ], Keap1/NRF2-ARE signaling pathway [ 77 ], and AMPK-NRF2 signaling pathway [ 78 ], all of which play a regulatory role on ferroptosis in specific cells.…”
Section: Mechanism Of Ferroptosis and Ferritinophagymentioning
confidence: 99%
“…That is, tagitin C induces ferroptosis through the activation of the PERK-NRF2-HO-1 signaling pathway mediated by ER [ 74 ]. In addition, there are other pathways related to NRF2 that regulate ferroptosis: GSK-3β/NRF2 signaling pathway [ 75 ], Akt/NRF2/HO-1 signaling pathway [ 76 ], Keap1/NRF2-ARE signaling pathway [ 77 ], and AMPK-NRF2 signaling pathway [ 78 ], all of which play a regulatory role on ferroptosis in specific cells.…”
Section: Mechanism Of Ferroptosis and Ferritinophagymentioning
confidence: 99%
“…These findings might lead to a novel therapeutic method for SCI. By stimulating the AKT/Nrf2/HO-1 signaling pathway, the anti-inflammatory mediator lipoxin A4 can reduce ferroptosis in spinal cord neurons [ 77 ]. Similarly, syringic acid [ 75 ], proanthocyanidins [ 73 ], and zinc [ 74 ] all reversed ferroptosis to varying degrees by activating the Nrf2/HO-1 pathway.…”
Section: Research Progress Of Ferroptosis In Scimentioning
confidence: 99%
“…On the other side, our previous results indicated that L-F001 could activate Nrf-2/HO-1 signaling (Luo et al, 2017 ), we also found that Nrf2/HO-1 signaling is activation under RSL-3 treatment rather than downregulation (Peng et al, 2021 ). Furthermore, some research demonstrated that many active compounds exhibit protection through further upregulation of Nrf2/HO-1 signaling (Gou et al, 2020 ; Wei et al, 2021 ; Fu et al, 2022 ), compared to the already increased Nrf2 signaling. Therefore Nrf2/HO-1 signaling activation might be an important part in L-F001 anti-ferroptosis role.…”
Section: Discussionmentioning
confidence: 99%